Primary breast lymphoma in males: Incidence, demographics, prognostic factors, survival, and comparisons with females - Zhang, Jie; Ma, Binbin; Ji, Hong; Guo, Rong (Frontiers in Surgery, 2022)
Background: Primary breast lymphoma (PBL) occurs very rarely and is mainly observed in females. None of male PBL cohorts was reported previously. This study aims to investigate the incidence, clinical characteristics, prognostic factors and survival outcome among male PBL patients, and also, to perform comparisons between males and females. Methods: Patients diagnosed with PBL between 2000 and 2019 from the Surveillance, Epidemiology, and End Results (SEER) database were identified. Age-adjusted incidence rates were calculated by year and age for trend analysis. Univariate and multivariate Cox hazard proportional regression was performed to identify prognostic factors. Survival comparisons were conducted using Kaplan-Meier method and log-rank test. Propensity matching score (PSM) method was used to balance demographics. Results: The incidence of 122 male PBL patients diagnosed from 2000 to 2019 was 0.169 (95%CI: 0.140-2.203) per million persons, much lower than that of 2,543 females (1.59, 95%CI: 1.53-1.65). Clinical demographics were similar between females and males except the lymphoma subtype distribution (P=0.025). A higher age (HR=1.08, 95%CI: 1.05-1.12, P<0.001) and not receiving radiotherapy (receiving vs not receiving: HR=0.41, 95%CI: 0.21-0.78, P=0.007) were significant risk factors associated with overall survival (OS) in males. Radiotherapy (OS: P=0.023) can offer benefits in OS. Using PSM method, we also firstly revealed that male PBL patients had significantly worse OS and cancer-specific survival than females. Conclusions: This study firstly analyzed male patients with PBL involving incidence, clinical characteristics and survival data. Sex disparity was also observed in the survival outcome of the disease.